The students’ awareness degree of the effectiveness of artificial intelligence applications in learning the Arabic language - Faqeeh, Mohammad Hussein; Al Aqtash, Salem Khalil; Musleh, Omran Ahmad; Alwaely, Suad Abdel Karim; Elzeiny, Mohamed Elsayed; Moath Khalaf Al Omery; Mostafa, Imad Ibraheem (Research Journal in Advanced Humanities, 2024)
This study aimed to identify the degree of students’ awareness of the effectiveness of artificial intelligence (AI) applications in learning the Arabic language, as students’ viewpoints can provide valuable insights into directing and modifying their behavior towards learning Arabic through their awareness of AI applications’ effectiveness. Data for this study were gathered by the researchers using a questionnaire and a descriptive approach. The study population consisted of 286 male and female students, while the study sample consisted of 175 male and female students, randomly selected from the study population. The questionnaire contained thirty items in total. The findings showed that the degree of students’ awareness of the effectiveness of AI applications in learning Arabic was high across all items, with an overall arithmetic average of 3.98. The arithmetic averages ranged between 3.67 and 4.26, with paragraph No. 15 ranked first with an arithmetic average of 4.26, while paragraph No. 13 ranked last with an arithmetic average of 3.67. The findings also indicated that gender did not result in any statistically significant differences. However, the results showed that the academic year had a statistically significant effect, with second-year students and above showing the greatest differences. Additionally, the data indicated that the type of college had a significant effect, with students from scientific colleges showing higher awareness.